1991
DOI: 10.1021/es00023a001
|View full text |Cite
|
Sign up to set email alerts
|

Long-term high and low-volume air sampling of polychlorinated dibenzo-p-dioxins and dibenzofurans and polycyclic aromatic hydrocarbons along a transect from urban to remote areas on the Swedish Baltic coast

Abstract: Air samples were collected along a transect from the city of Stockholm urban area to the open coastal area of the Baltic Sea. Samples for polycyclic aromatic hydrocarbon (PAH) and polychlorinated dibenzo-p-dioxin and dibenzofuran (PCDD/F) analysis were collected for 135 days (mean 860 m3) and for 5-64 days (6500-5400 m3), respectively. The concentrations were found to decrease with increasing distance from Stockholm with intervals of total concentrations of 1.4-0.2 pg/m3 (24-3 fg of toxic equiv/m3) for the PCD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(33 citation statements)
references
References 35 publications
4
29
0
Order By: Relevance
“…Details on the sampling site and meteorological conditions can be found elsewhere (Krecl et al, 2007(Krecl et al, , 2008a. Two custom-built highvolume samplers were employed (Broman et al, 1991), each one consisting of an inverted filter holder which collected total suspended particle matter (TSP) on borosilicate glass fiber filters (GFF, 293 mm diameter, Millipore, USA). Downstream of the GFF filters were two sequential polyurethane foam (PUF) traps for collecting volatile compounds.…”
Section: Sample Collection and Treatmentmentioning
confidence: 99%
“…Details on the sampling site and meteorological conditions can be found elsewhere (Krecl et al, 2007(Krecl et al, , 2008a. Two custom-built highvolume samplers were employed (Broman et al, 1991), each one consisting of an inverted filter holder which collected total suspended particle matter (TSP) on borosilicate glass fiber filters (GFF, 293 mm diameter, Millipore, USA). Downstream of the GFF filters were two sequential polyurethane foam (PUF) traps for collecting volatile compounds.…”
Section: Sample Collection and Treatmentmentioning
confidence: 99%
“…These four-ringed compounds are among the most abundant PAHs in creosote wood preservative (Elder and Dresler 1988). Fluoranthene also tends to be a dominant PAH in atmospheric deposition (Broman et al 1991), and pyrene and chrysene are among the more common PAHs found in motor vehicle particulate emissions. Four other PAHs were detected in approximately 7 to 8 percent of the samples at Camp Edwards: benzo(b)fluoranthene, benzo(k)fluoranthene, benzo(a)anthracene, and benzo(a)pyrene.…”
Section: Semi-volatile Organic Compounds (Svocs)mentioning
confidence: 99%
“…So is the German median deposition at background stations, 3 pg I-TEq m -2 d -1 (BLAD 2002a). Broman et al (1991a) and Tysklind et al (1993) reported that 4-PeCDF makes up c. 20 % of the total TEq in air at rural Swedish coastal sites.…”
Section: Atmospheric Depositionmentioning
confidence: 99%
“…estimated from unpublished data the background Swedish atmospheric deposition flux of dlPCBs at 0.04 ng WHO-TEq P m -2 , i.e. 2 % of the flux of WHOTEq DF based on data by Broman et al (1991a), and amounting to 15 g WHO-TEq P a -1 on Baltic Sea surface. However, the following factors have to be borne in mind in evaluating these data:…”
Section: Atmospheric Depositionmentioning
confidence: 99%
See 1 more Smart Citation